2011
DOI: 10.1128/aem.00649-11
|View full text |Cite
|
Sign up to set email alerts
|

Possible Overestimation of Surface Disinfection Efficiency by Assessment Methods Based on Liquid Sampling Procedures as Demonstrated by In Situ Quantification of Spore Viability

Abstract: The standard test methods used to assess the efficiency of a disinfectant applied to surfaces are often based on counting the microbial survivors sampled in a liquid, but total cell removal from surfaces is seldom achieved. One might therefore wonder whether evaluations of microbial survivors in liquid-sampled cells are representative of the levels of survivors in whole populations. The present study was thus designed to determine the "damaged/undamaged" status induced by a peracetic acid disinfection for Baci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Our general observation was that the heterogeneity of the biomass in the wells increased dramatically over time as each developed seemingly stochastically differently, depending on the microenvironment in the individual well. This heterogeneous growth may contribute to the deviations often found in this model as the local microenvironment in each well may influence growth, strength, and resilience [ [23] , [24] , [25] ].…”
Section: Discussionmentioning
confidence: 99%
“…Our general observation was that the heterogeneity of the biomass in the wells increased dramatically over time as each developed seemingly stochastically differently, depending on the microenvironment in the individual well. This heterogeneous growth may contribute to the deviations often found in this model as the local microenvironment in each well may influence growth, strength, and resilience [ [23] , [24] , [25] ].…”
Section: Discussionmentioning
confidence: 99%
“…First, only a fraction of the sessile community can be suspended by sonication, typically between 5% and 90% of the community (Edmonds et al, 2009;Muller et al, 2011). Second, the physiological properties of the detached population may not reflect the physiology of sessile cells, as different populations could exhibit different adhesive and detachment properties on the material (Grand et al, 2011). In both microtiter tray based assays, the pegs or wells can further be coated with different molecules to investigate or promote biofilm formation to different biotic and abiotic supports.…”
Section: Microtiter Platesmentioning
confidence: 99%
“…It has been suggested that for instances in which the recovery of microorganisms from test materials is <100%, the disinfection efficacy could be overestimated. 11 In the present study, recovery of B mallei after 1 hour of drying ranged from 79% to 86% for all 3 test materials. Therefore, it is possible that a similar overestimation may occur when assessing persistence with an extraction-plating procedure.…”
Section: Discussionmentioning
confidence: 44%